The double agent: aspects of literary translator affect as revealed in fictional work by translators - Anderson, Jean (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
How do translator-authors represent translators and the translation act in fiction? What do such works indicate about the affective aspects of translation and literary translation in particular? This introductory survey of these issues analyses several fictional works written by translators, to show that certain emotional responses recur , and that while there is little research into affect and literary translation, there are elements commonly found in studies of bilingualism which are echoed in the works of fiction studied. Whether these echoes can be construed as constituting a psychological profile of the literary translator is a moot point; what does emerge clearly is a literary representation of a profession whose members are marginalised, trans gressive, even fraudulent or impostors; at the very least, prey to identity instability.